Scenario-Based Approaches to Change Management in Fisheries Can Address Challenges With Scale and Support the Implementation of an Ecosystem Approach to Fisheries Management - Gammage, Louise Carin; Jarre, Astrid (Frontiers in Marine Science, 2021)
The Ecosystem Approach to Fisheries (EAF) management, recognising complexity, aims for the holistic, sustainable management of fisheries to promote healthy marine ecosystems and sustainable livelihoods. Effective implementation of the EAF has been problematic as we continue to grapple with issues of scale, knowledge integration and meaningful stakeholder engagement. Scenario-planning approaches in marine social ecological systems (SES) can address some of these challenges. Using systems-thinking, scenario-planning presents the opportunity to address challenges simultaneously at different scales of interaction by addressing the needs at smaller and larger decision-making scales. We here present a prototype scenario-based approach in which we used structured decision-making tools (SDMTs) in an iterative and interactive research process with marginalised stakeholders in a small-scale fishery in South Africa’s southern Cape. Using this approach presented an opportunity for fishers to consider pathways for future responses to change while enhancing personal and local adaptive capacity. At the same time, these marginalised fishers were provided with an important opportunity to freely air their views while engaging with tools new to them. The process did not only benefit fishers, but also provided valuable insights into how they view and experience their marine SES. The use of these tools has provided a means to integrate different knowledge streams, identifying ways in which challenges presented by scale in SES is better addressed. As a next step in the prototype development, expansion to more diverse stakeholders in the biogeographical region relevant for this fishery is recommended. We highlight how this approach can contribute to multi-level governance. When considering EAF implementation, we highlight how engaging marginalised stakeholders need not mean losing the reproducible, transparent processes required for modern management. Lastly, we discuss how multi-scalar flow of information could improve the implementation of an EAF in a developing society, such as that of South Africa.